1994
DOI: 10.1037/0012-1649.30.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of stressful life events and depressive symptoms during adolescence.

Abstract: This 4-year longitudinal study of 191 girls and 185 boys living in intact families in the rural Midwest examines the trajectories of life events and depressive symptoms in adolescence. The trajectories of depressive symptoms differ between boys and girls. Compared with boys, girls experienced a greater number of depressive symptoms after age 13. Changes in uncontrollable events are associated with the increases in girls' but not boys' depressive symptoms. Latent growth curve analyses show that, over 4 years, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

77
652
19
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(756 citation statements)
references
References 65 publications
77
652
19
8
Order By: Relevance
“…However, at adolescence, girls overall show an increase in depressive symptoms, whereas boys tend to experience fairly stable or slightly decreasing levels of symptoms (e.g., Garber, Keiley, & Martin, 2002;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;Ge, Lorenz, Conger, Elder, & Simons, 1994;Ge, Conger, & Elder, 2001;Kim, Capaldi, & Stoolmiller, 2003). For the current sample, using a latent growth curve approach, Kim et al (2003) found that the mean level of depressive symptoms in young men slightly decreased from early adolescence (ages 14-15 years) through young adulthood (ages 23-24 years).…”
Section: Heterogeneity Of Trajectories Of Depressive Symptoms Across mentioning
confidence: 66%
See 1 more Smart Citation
“…However, at adolescence, girls overall show an increase in depressive symptoms, whereas boys tend to experience fairly stable or slightly decreasing levels of symptoms (e.g., Garber, Keiley, & Martin, 2002;Garrison, Jackson, Marsteller, McKeown, & Addy, 1990;Ge, Lorenz, Conger, Elder, & Simons, 1994;Ge, Conger, & Elder, 2001;Kim, Capaldi, & Stoolmiller, 2003). For the current sample, using a latent growth curve approach, Kim et al (2003) found that the mean level of depressive symptoms in young men slightly decreased from early adolescence (ages 14-15 years) through young adulthood (ages 23-24 years).…”
Section: Heterogeneity Of Trajectories Of Depressive Symptoms Across mentioning
confidence: 66%
“…For the current sample, using a latent growth curve approach, Kim et al (2003) found that the mean level of depressive symptoms in young men slightly decreased from early adolescence (ages 14-15 years) through young adulthood (ages 23-24 years). Using multicohort longitudinal data, Ge and colleagues (Ge et al, 1994) also found that boys' trajectories tended to be relatively flat over time, whereas girls' trajectories showed a sharp increase between the ages of 12 and 15 years. Interestingly, these studies also suggested significant variations in the average levels of depressive symptoms across time in young men.…”
Section: Heterogeneity Of Trajectories Of Depressive Symptoms Across mentioning
confidence: 97%
“…When not experiencing a negative mood, cognitions related to negative affect may be inactive. Adolescents may experience more negative life events than children (e.g., Ge et al, 1994), offering opportunities for latent cognitive schemata to become activated. The lower average rates of stress in early childhood raise the possibility that cognitive vulnerability factors may be present, but not activated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the presence of negative life events is a reliable risk factor for the development of depressive symptoms in both sexes equally [14]. In adolescence, girls are exposed to a higher risk of developing symptoms of depression because it is assumed that they experience more negative life events (especially in interpersonal domains) and are more sensitive to stressful events, such as, for example, conflicts with peers [15,16].…”
Section: Social Support and Negative Life Events (Stressors)mentioning
confidence: 99%